Drunktown's finest - Orton, Mark ca. 20. Jh; Pickard, Joel (NeHST, 2015)
On a beautifully desolate Navajo reservation in New Mexico, three young people, a college-bound, devout Christian woman; a rebellious and angry father-to-be; and a promiscuous but gorgeous transsexual woman, search for love and acceptance. As the three find their lives becoming more complicated and their troubles growing, their paths begin to intersect
Originally released as motion picture in 2014
"From executive producer Robert Redford"--Container
Extras include music and deleted scenes
Keywords: Navajo youth / Drama; Navajo Indians / Drama; Adoptees / Drama; Two-spirit people / Drama; Two-spirit people; Adoptees; Navajo Indians; Navajo youth; DVD-Video discs; Feature films; Fiction films; Drama; Film; DVD-Video